Health-promoting and health-constraining environmental features and physical activity and sedentary behaviour in adolescence: a geospatial cross-sectional study. (September 2022) - Hobbs, M.; Stewart, T.; Marek, L.; Duncan, S.; Campbell, M.; Kingham, S.
Abstract: The environment may be an important influence on adolescent behaviour. We combined accelerometry and global positioning system data to investigate how the environment was related to physical activity and sedentary behaviour. Adolescents spent most of their time in very close proximity to a range of both health-promoting and health-constraining features. Several associations were detected between time spent in areas with the greatest access to health-promoting features and reduced sedentary time and less travel time by motor vehicle. The environment may contribute to the variation in adolescent activity behaviour. Highlights: Where adolescents spend their time may impact on their health behaviours. Best access to health-promoting environments was related to less sedentary time. Worst access to health-promoting environments was related to more vehicle travel.